Retinoid X receptor ligands: a patent review (2007 – 2013). (April 2014) - Yamada, Shoya; Kakuta, Hiroki
<x xml:space="preserve">Abstract</x> Introduction: Retinoid X receptors (RXRs) are nuclear receptors that act as ligand-dependent transcription factors. RXRs function as homodimers or as heterodimers with other nuclear receptors, such as retinoic acid receptors, PPARs, liver X receptors, farnesoid X receptor, vitamin D receptor or thyroid hormone receptors. RXR ligands (agonists or antagonists) show various physiological effects, depending on their partner receptors. RXR agonist bexarotene (Targretin®) is used for the treatment of cutaneous T-cell lymphoma in clinical practice. RXR agonists were also reported to be useful for treatment of type 2 diabetes, autoimmune disease and Alzheimer's disease. RXR antagonists were also reported to be effective in type 2 diabetes treatment. Areas covered: Here patent applications (2007 – 2013) concerning RXR ligands are summarized, and the usefulness of RXR ligands as pharmaceutical agents is discussed. Expert opinion: RXR agonists show a wide variety of biological effects. However, they cause serious side effects, such as blood triglyceride elevation, hypothyroidism and others. Thus, for clinical application of RXR agonists, abrogation of these side effects is required. RXR heterodimer-selective agonists and RXR partial agonists exhibiting desired effects without side effects are expected to find clinical application.